L’habitant et son territoire dans les procédures d’aménagement : l’exemple de projets éoliens dans l’Allier et dans le Vaucluse, France - Pierre Pech; Cécile Gauthier; Justine Muller; Delphine Giney; Hélène Sirota-Chelzen (VertigO)
This article explores the relationship between people living in a territory and their territory in the specific case of development projects. We focus here on two cases of wind infrastructure development projects in sparsely populated areas in France. Environmental Impact Assessment (EIA) has become a regulatory process in most countries. This procedure includes surveys of the inhabitants of the areas affected by infrastructure projects. The survey carried out in two rural areas, in the French departments of Allier and Vaucluse, concerns the relations between the representations of the inhabitants relating to wind energy and their representation of their territory. The statements of the interviewed persons allow opposing the representations that the inhabitants have over their territory. In the Allier, the landscape is felt to be poor, downgraded because most of the inhabitants and part of the built heritage preserve the memory of an industrial activity considered to have made the territory dynamic. The landscape's visual object, "wind turbine," is not considered unfavourable because it represents a positive image of the territory. On the other hand, in Haute Provence, the inhabitants, for the most part, neo-retired or secondary residents on the outskirts of large cities, see wind turbines negatively.